The autism spectrum : scientific foundations and treatment - Reber, Mark (Cambridge University Press, 2012)
"Written for the wide range of physicians and professionals who treat children and adults with autism spectrum disorders (ASDs), this book reviews the scientific research on the nature and causes of autism, outlines best treatment practices with children and describes a comprehensive assessment and treatment approach for adults. Topics covered include: [bullet] Classification, epidemiology and diagnosis [bullet] Neurodevelopmental abnormalities [bullet] Recommendations for early screening and evaluating at-risk children [bullet] Early interventions based on applied behavioral analysis [bullet] The critical role of special education, speech-language therapy, occupational therapy and assistive technology in treating children [bullet] Pharmacotherapy [bullet] Complementary and alternative treatments [bullet] Development of individualized and person-centered treatments for adults The Autism Spectrum is an invaluable resource for all those working with ASDs including pediatricians, psychiatrists, behavioral psychologists, special educators, nurses and therapists"-- Provided by publisher